The The Effect Of Paitan (Thithonia Diversifolia L.) POC And Medium Of Fertilizer Plants ON The Growth and Production OF Pagoda Palm Plant (Brassica Nanirosa L.) - Andriani Eko Prihatiningrum; Achmad Billyardi (Universitas Muhammadiyah Sidoarjo, 2020)
The research was conducted in the village jiken tulangan sidoarjo. especially mustard pagoda still needed, opening up opportunities in the production of organic farming, which supports the public demand for mustard pagoda, pagoda mustard plants can respond to the growth and yield of mustard pagoda. as organic materials, this study aims to determine the effect of dose poc paitan and cow manure on the growth and yield of mustard pagoda. as well as to determine the dose poc paitan and cow manure is right at pagoda mustard growth in order to obtain the highest yield, The experiment was arranged in factorial design used was a randomized block dsign (RAK) first factor E0,E1,E2 and the second factor B1, B2. B3 repeated 3 replications and 9 treatments each test and the test continued HSD 5% The result of research show that dosing poc paitan and cow manure average – highest average on observation of plant height, leaf number, stem diameter, leaf area, fresh weight, dry weight and root showed the highest at treatment E1 = cow manure 100 gr (20 ton/ ha) and B= POC paitan 25ml/ltr.